2018
DOI: 10.1158/0008-5472.can-17-2020
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating Neuropilin-2 Triggers a Novel Mechanism Enabling EGFR-Dependent Resistance to Oncogene-Targeted Therapies

Abstract: Neuropilins are a class of cell surface proteins implicated in cell migration and angiogenesis, with aberrant expression in human tumors. Here, we show that the expression of Neuropilin-2 (NRP2) controls EGFR protein levels, thereby impinging on intracellular signaling, viability, and response to targeted therapies of oncogene-addicted cells. Notably, increased NRP2 expression in EGFR-addicted tumor cells led to downregulation of EGFR protein and tumor cell growth inhibition. NRP2 also blunted upregulation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Pathway enrichment analyses showed that NRP-2 mediates tumor progression through multiple oncogenic signaling pathways including EGFR, CCKR, angiogenesis and various growth factors (VEGF, FGF, PDGF) signaling axes. EGFR signaling enrichment upon NRP-2 expression contrasts with a report showing that the acquisition of resistance to therapy in MET-addicted cancer cells is dependent on NRP-2 downregulation [47]. This question was not addressed in our study since MET levels are almost undetectable in our models.…”
Section: Discussioncontrasting
confidence: 76%
“…Pathway enrichment analyses showed that NRP-2 mediates tumor progression through multiple oncogenic signaling pathways including EGFR, CCKR, angiogenesis and various growth factors (VEGF, FGF, PDGF) signaling axes. EGFR signaling enrichment upon NRP-2 expression contrasts with a report showing that the acquisition of resistance to therapy in MET-addicted cancer cells is dependent on NRP-2 downregulation [47]. This question was not addressed in our study since MET levels are almost undetectable in our models.…”
Section: Discussioncontrasting
confidence: 76%
“…Neuropilin 2 overexpression decreases EGFR expression and resistance to MET-targeted therapies (Rizzolio et al, 2018a).…”
Section: Resistance To Targeted Therapiesmentioning
confidence: 99%
“…SEMA3s and their receptors have been reported to be related with drug responses in a number of cancer types [3,[59][60][61]. We next investigated the expression of NRPs and PLXNs in NCI-60 cell lines and systematically tested the correlation between their expression levels with drug sensitivity score of over 200 chemotherapy drugs.…”
Section: Neuropilins and Plexins Are Associated With Tumor Stemness Amentioning
confidence: 99%